POLITICAL REPRESENTATION INNOVATION: A CASE STUDY OF “RUMAH ASPIRASI RAKYAT AAM AMARULLOH” IN CILEGON CITY - Dewi, Shanty Kartika; Fuad, Anis; Amelia, Tia; Putri, Siti Saratipo Hemalia; Salsabila, Sinisa Safa (JWP (Jurnal Wacana Politik), 2025)
This study examines the politics of representation of the “Rumah Aspirasi Rakyat Aam Amarulloh” in representing the people’s aspirations in Cilegon City. This Aspiration House is an intermediary space between constituents and legislators, facilitating communication and conveying public aspiration. The research method used is qualitative research with a case study approach. Data were obtained through in-depth interviews and direct observation of activities at the Aspiration House. The research results show that around 80% of the aspirations collected have been responsively followed by the relevant legislator, Aam Amarulloh. These findings indicate that “Rumah Aspirasi Rakyat Aam Amarulloh” effectively facilitates the public in conveying their complaints and aspirations. Furthermore, the residents in electoral district 3 Cilegon Municipal, which includes the Pulomerak and Grogol districts, express a deep sense of satisfaction with the performance of this Aspiration House. Thus, this study provides empirical evidence that the descriptive representation model applied in this Aspiration House can enhance public participation and representation in the legislative process. The study also suggests that further development is needed to improve some aspects that are still less optimal.